Media Ideology and Representation of The National Police Image in The Online Media Frame (Framing Analysis of Teddy Minahasa Drug Case in the October 15, 2022 Edition of Koran Tempo Online) - Dela Sulistiyawan Yunior (International Journal of Social Service and Research, 2023)
One of the advantages of online journalism compared to conventional media is accessibility and speed in getting news. However, despite these advantages, online news portals are not automatically superior to conventional media in terms of the value of journalism products or news content. However, media ideology is very influential in the process of news construction, especially through the framing of news. No exception about the news of the drug case that is entangling a Two-Star Police General, Teddy Minahasa, of course, the media is interested in reporting the issue. The method used in this study includes framing analysis developed by Pan and Kosicky, while the approach used is qualitative. In this study, results were obtained that showed that the online tempo newspaper in reporting the tragedy was critical, informative and provocative. This indication can be seen from the results of the framing analysis carried out, namely the main framing of the news is that a Two-Star General is entangled in drugs is a controversial thing and certainly damages the institution of the National Police. With syntactic elements is the strengthening of framing by using unbalanced source quotes so that they are not neutral in reporting. As for the script element, strengthening and enriching the news paragraph related to the How element is carried out to minimize the why element in the news. For thematic elements, there are 3 major themes, namely: 1. A Two-Star General Dragged into a Drug Case 2. Chronology of occurrence of the case 3. Suppression of the negative image of the Indonesian National Police. In addition, the selection of sources as a closing news, to emphasize that the condition of the National Police organization is very bad, is used as a whip for the National Police institution to improve its organization. The last is the rhetorical element, in this element the use of newspaper covers and some graphics to emphasize the element of news that seems hyperbole and provocative and even seems negative. In addition, it can be concluded that the tempo tempo online newspaper according to its media ideology constructs reality through a framing process for the purpose of representing the negative image of the Indonesian National Police in a news story.